EVALUATION THE EFFECT OF NANOTECHNOLOGY ON PHARMACEUTICAL AND BIOLOGICAL PROPERTIES OF METRONIDAZOLE - from publication on author’s request, This article has been withdrawn (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
This article has been withdrawn from publication on author’s request